Biossíntese de nanocompósitos fotoativos de Fe3O4@ZnO decorados com Cu e Ni para a degradação do corante Rodamina B - Prescilio, Isabella Cristina (2024)
The textile sector produces approximately 700 million kilograms of dyes per year, of which about 10 to 20% are improperly discharged into the environment without prior treatment. Contamination of effluents by industrial dyes adversely affects aquatic ecosystems and threatens human health. In this context, the present study aims at the economically and ecologically sustainable biosynthesis of Fe3O4@ZnO, Fe3O4@ZnO-Cu and Fe3O4@ZnO-Ni nanocomposites, using hydroethanolic extract and infusion from the leaves of Magonia pubescens A. St. Hil. Results obtained by XPS and XRD confirmed the crystalline structure and atomic composition of the nanocomposites. TEM analysis evidenced the presence of Fe3O4, ZnO, Cu and Ni in the material, with minor agglomerations. Particle size distribution histograms derived from TEM images revealed average size of 14 nm, 6,5 nm, and 6,99 nm for Fe3O4@ZnO, Fe3O4@ZnO-Cu and Fe3O4@ZnO-Ni nanocomposites, respectively, as well as average sizes of 4,96 nm, 6,5 nm, 8,48nm, and 14 nm for Fe3O4, CuO, NiO and ZnO nanoparticles, respectively. EDS analyses confirmed the presence of Zn, Cu, Ni, Fe and O elements in each material. The band gap energy evaluated by UV-Vis spectroscopy presented values of 3,46eV, 3,17 eV, 2,82 eV and 2,46 eV for ZnO, Fe3O4@ZnO, Fe3O4@ZnO-Cu and Fe3O4@ZnO-Ni, respectively. Moreover, each biosynthesized nanocomposite was evaluated for its ability to photodegrade rhodamine B under visible light irradiation for 300 minutes. The results indicate that the Fe3O4@ZnO-Ni nanocomposite (96,8%) showed superior photodegradation efficiency compared to Fe3O4@ZnO (87,5%) and Fe3O4@ZnO-Cu (55,6%) nanocomposites.